Detection of mecA and enterotoxin genes in Staphylococcus aureus isolates associated with bovine mastitis and characterization of Staphylococcal cassette chromosome mec (SCCmec) in MRSA strains. - Havaei, Seyed Asghar (Iran J Microbiol, 2015)
BACKGROUND AND OBJECTIVES: Staphylococcus aureus is one of the main causatives of bovine mastitis. Resistance of some strains to methicillin, can complicate the treatment of its infections. On the other hand, enterotoxin production is also important. Therefore, the aim of our study was to investigate the methicillin resistance and enterotoxin production in S. aureus isolates caused bovine mastitis. MATERIALS AND METHODS: Four hundred and fifty milk samples were collected. After isolation of Staphylococcus aureus, MRSA strains were detected by cefoxitin disc diffusion and oxacillin agar screening methods. DNA was extracted by phenol – chloroform method and PCR was applied for mecA, sea and seb genes. SCCmec types of mecA gene were identified using multiplex-PCR. RESULTS: Fifty-four (12%) S. aureus were isolated. Out of these, 10 and 9 MRSA strains identified by cefoxitin disc diffusion and oxacillin agar screening methods, respectively. All 10 MRSA isolates identified by cefoxitin disc diffusion, were positive for mecA gene and all of them belonged to SCCmec type IV. The sea genes were detected in 19 isolates and only two isolates were positive for seb genes. One isolate possessed both sea and seb genes. CONCLUSION: Findings of this study indicated that results of cefoxitin disc diffusion test is in concordance with the PCR for mecA gene and has a higher sensitivity compared to oxacillin agar screening method. Finally, Our findings suggest that enterotoxin A is the dominant type.